ALTERNATIVE MEDIA FOR BACTERIAL GROWTH STAPHYLOCOCCUS AUREUS: SWEET POTATO INFUSA (IPOMOEA BATATAS), SOYBEANS (GLYCINE MAX (L) MERRILL) AND YEAST EXTRACT - Martsiningsih, Marta Atik; Astuti, Fardhiasih Dwi; Sistiyono, Sistiyono; Suyana, Suyana; Rahmawati, Ullya; Rahayu, Muji; Musyafaah, Novita Siti (Meditory : The Journal of Medical Laboratory, 2024)
Background: Staphylococcus aureus needs nourishment for its growth. The needed nutrients of carbohydrates, proteins, nitrogen, vitamins, and minerals from the media. The media commonly used for bacterial growth is the nutrient medium for high prices. Alternative media from natural local foodstuffs are obtained easily and cheaply instead of instant media. This study aims to identify alternative media mixed with infuse sweet potato (ipomoea batatas), soybeans (glycine Max (l) Merrill), and yeast extract that can be used to grow the staphylococcus aureus bacteria.  Methode: this type of research is pure experimental research, and the design used is the posttest-only control design group. Staphylococcus aureus suspension was grown on alternative media and nutrient agar media as a comparison. measurements of colony diameter and number of colonies were compared between alternative media and nutrient agar. Result The results Research has provided an average number of staphylococcus aureus bacteria that grow on alternative media 78.00 x 104 CFU /ml and nutrient media for 94.19 x 104 CFU /ml. Whereas the colony's diameter of alternative media 2.56 mm, and the media nutrient increased by 2.66 mm. Conclusion: Alternative media from a blend of yam, soy infuse, and yeast extract can be used for the growth of the staphylococcus aureus bacteriaKeywords: Staphylococcus aureus; Alternative Media; Potato Infusa; soy infuse; soy infuse